Wildness, eschatology, and enclosure in the songs of Townes Van Zandt - MacDonald, Michael B. (My University, 2013)
An analysis of songs by Townes Van Zandt chronicling late twentieth-century American culture amid significant social and economic change.
Keywords: Townes Van Zandt; American culture; country music; J. G. Herder